Stellar libraries for Gaia - Sordo, Rosanna; Vallenari, Antonella; Tantalo, R.; Liu, Chao; Smith, K.; Allard, France; Blomme, R.; Bouret, J-C; Brott, I.; De Laverny, P.; Edvardsson, B.; Fremat, Y.; et al. (Journal of Physics: Conference Series, 2011)
Gaia will observe up to a billion stellar sources. Automated algorithms are under development to derive the atmospheric parameters of all observed spectra, from low resolution optical spectra alone or in synergy with high resolution spectra in the near-IR Ca II triplet region. To do so, a large database of state-of-the-art stellar libraries has been produced for the Gaia community, computed using different codes optimized for specific purposes. The choice to use different spectral codes in different regions of the H-R diagram raises the problem of the coherence of the different spectra, specifically in the transition zones. We present a comparison between the libraries from the point of view of spectra simulations for training the Gaia algorithms. We also present the implementation of these libraries into a Simple Stellar Population code.
CRIS-Team Scopus Importer:2020-12-21